Long-run Fiscal Projections under Uncertainty: The Case of New Zealand - Christopher Ball; John Creedy; Grant Scobie (New Zealand Government, The Treasury, 2015)
This paper introduces uncertainty into a fiscal projection model which incorporates population ageing along with a number of feedback effects. When fiscal policy responds in order to achieve a target debt ratio, feedback effects modify the intended outcomes. The feedbacks include the effect on labour supply in response to changes in tax rates, changes in the country risk premium in response to higher public debt ratios, endogenous changes in the rate of productivity growth and savings. Stochastic projections of a range of policy responses are produced, allowing for uncertainty regarding the world interest rate, productivity growth and the growth rates of two components of per capita government expenditure. The probability of exceeding a given debt ratio in each projection year, using a particular tax or expenditure policy, can then be evaluated. Policy implications are briefly discussed.
Keywords: 330; Finanzpolitik; Öffentliche Finanzen; Prognose; Risiko; Neuseeland